A Neurodynamic Perspective on Musical Enjoyment: The Role of Emotional Granularity - Barrett, Nathaniel F.; Schulkin, Jay (Frontiers in Psychology, 2017)
This article explores how an emerging family of neurodynamic theories of brain function could be extended to offer a new perspective on musical enjoyment that highlights the role of emotional granularity in musical experience and invites new paths of empirical research. Music perception is an active area of neurodynamic research but few studies of musical enjoyment are based on a neurodynamic approach; meanwhile few if any scientific discussions of musical enjoyment take emotional granularity into account. Here we focus on the paradoxical phenomenon of enjoyable sadness in music in order to develop the explanatory prospects of a neurodynamic approach that incorporates emotional granularity. Studies have indicated that higher emotional granularity can have a meliorating effect on the experience of negative emotion, and we propose that high emotional granularity is what accounts for the enjoyment of sadness in music. Furthermore, we suggest a broad distinction between pleasure, defined as bursts of positively categorized feeling, and enjoyment, defined as sustained flows of highly differentiated feelings regardless of emotional categorization.